How clients' during-treatment motivations relate to their perceptions and impressions of methadone maintenance treatment: A multilevel analysis of a cross-sectional survey in Guangdong Province, China. (1st July 2016) - Deng, Liwei; Zou, Xia; Chen, Wen; Xia, Yinghua; Liu, Yu; Ling, Li
Highlights: There is a need for improving during-treatment motivation among Chinese methadone maintenance treatment (MMT) clients. Besides education, clients' perceptions and impressions of MMT relate to motivation. Supportive family assistance and closing time relate to motivation at clinic level. Abstract: Background: Much evidence has suggested the positive effect of methadone maintenance treatment (MMT) on mitigating adverse outcomes caused by opioid use. Pretreatment motivations are associated with clients' engagement, retention, and outcomes in drug use treatment. However, motivation is mutable, and few MMT researchers have considered during-treatment motivations and associated multilevel factors. Objective: We aimed to investigate during-treatment motivations and clinic- and individual-level associated factors among MMT clients in Guangdong Province, China. Methods: Stratified random sampling was used to select 12 MMT clinics in Guangdong Province. Between December 2011 and January 2012, a total of 802 respondents were surveyed about their motivation and multilevel factors using the following instruments: the Texas Christian University (TCU) Treatment Motivation Scales, the impression-of-detoxification scale, the National MMT Data Management System of China, and structured questionnaires. Multilevel models were employed to conduct the univariate and multivariate analyses of the factors associated with during-treatment motivations for MMT. Results: The means ± SD (95% CI) of clients' during-treatment motivations (Desire for Help and Treatment Readiness) were 2.89 ± 0.56 (2.85, 2.93) and 2.28 ± 0.57 (2.24, 2.32). Multilevel analyses showed that clients' educational level, perceptions, and impressions of MMT; and clinics' supportive family assistance and closing time were significantly associated with during-treatment motivations for MMT (P < 0.05). Conclusions: During-treatment motivation may play a significant role in the success of MMT. There is a need for improving motivation among Chinese MMT clients, and the knowledge of associated factors may guide more effective program in the future.